The occurrence of ochratoxin A in white and parboiled rice - Jakub Toman; František Malíř; Vladimír Ostrý; Yann Grosse; Vladimír Dvořák; Tomáš Roubal; Lucie Neuchlová (Czech Journal of Food Sciences, 2016)
The levels of ochratoxin A (OTA), one of the five agricultural and toxicological most important mycotoxins, have been determined by HPLC with fluorescence detection (HPLC-FLD) or enzyme-linked immunosorbent assay (ELISA) in 60 samples of white and parboiled rice, purchased on the Czech food market. In all 60 samples of rice tested by HPLC-FLD. OTA levels were below the limit of quantification (LOQ), i.e. < 0.2 ng/g. The same samples were also tested by ELISA (LOQ = 0.05 ng/g), and 58 samples (96.7%) were found to be positive. OTA levels in white and parboiled rice ranged from 0.05 to 0.17 ng/g; the arithmetic mean for all samples was 0.15 ng/g, the median 0.15 ng/g, and the 90% percentile 0.17 ng/g. These findings confirm the necessity of monitoring OTA in different foodstuffs and food, due to the precautionary principle and the uncertainty in the genotoxicity status of OTA.